Detection and identification of gastrointestinal microsporidia isolates from orang asli populations in peninsular Malaysia / Mohamad Haikal Mohamad Shah - Mohamad Shah, Mohamad Haikal (2015)
Microsporidia was recognized to cause intestinal disease not only in immunocompromised patient but also in immunocompetent person. Enterocytozoan bieneusi and Encephalitozoon intestinalis were the two most common species that causing infection in human. The specific tomes of transmission for microspon'dia may represent the risk factors which have not been documented specifically. However, several evidence explains multiple routes of microsporidial infections including waterborne, respiratory, anthroponon'c and zoonotic. Therefore, this study was conducted to determine the species-specific prevalence of microsporidia. sociodemographic, soda-economic characteristics and other possible risk factors associated with microsporidiosis among Orang Asli in Peninsular Malaysia. A sari“ of cross sectional study were carried out among different Orang Asli tribes in three states (Pahang, Perak Negeri Sembilan) within peninsular Malaysia Four hundred and fourty seven stool ,' were r " ’ and r 1‘y ’ ‘ for microsporidia spores after staining with Gram-chromotrope Kinyoun. Pre-tested questionnaire was used for collecting demographic, socioeconomic, environmental and behavioral data and further analysis using Pearson‘s Chi-square, univariate and multivariate analyses. Overall, 67 (15%) samples were detected positive for microsporidia. Funhennore, Encephalimzoan intestinalis was the only species distinguished in this study (2/67). The prevalence of microsporidia was found statistically significantly among individuals aged 2 15 years old compared to their counterparts (OR = 1.97, 95% CI = 1.08, 3.62; p = 0.028). Univariate and multivariate analyses confirmed that the presence of other members infected with microsporidia (OR = 8.45; 95% CI = 4.30, 1662; p = 0.001) and being a consumer of raw vegetables (OR = .05; 95% C] = 1.15, 3.66; p = 0.016) were the significant risk factors of microsporidiosis. The present findings indicate that exposure to microsporidia is common among Orang Asli population in Peninsular Malaysia This result in raising question if it represent true infection resulting from shedding of parasites or ingested parasites that only pass through the gastrointestinal without causing an infection to the host Successful amplification of E. intestinalis is an important finding and further studies by using specific primers for other microsporidia species must be conducted. Hence, Orang Asli in Malaysia must be provided with proper educational on healthcare in order to improve their quality of life. Screening of other family members should also be recommended as one of the strategies in controlling microsporidia infection in all Orang Asli tribes communities as one of the important risk factor was an infected family members.